Diversion et création d’échanges commerciaux dans le cadre du système canadien de préférences tarifaires - Ahmad, Jaleel (L'Actualité économique, 1979)
This paper explores in quantitative terms the potential effects on trade flows as a result of Canadian tariff preferences in favor of the developing countries instituted in 1974. The paper develops a model of trade creation and trade diversion due to preferences based on imperfect substitution, within each product category, between preference-granting, preference-receiving and non-preferred countries. This model depart from the usual assumption of the customs union theory that countries trade in perfect substitutes. The model is then applied to the 1978 trade date under BTN chapters 25 - 99 on a 4-digit classification. One major conclusion of the paper is that the assumption of perfect substitution tends to overstate the magnitude of trade creation and trade diversion, while the method based on less than perfect substitutability seems to offer more realistic estimates of the actual impact of trade preferences.